Studies on Socio-demographic Characteristics of Fungal Diseases Patients Attending at Out Patient Department of Rajshahi Medical College Hospital (KYAMC Journal, 2017)
A total of 12,798 fungal diseases patients were interviewed about their socio-demographic characteristics attending the Skin and V.D. department of Rajshahi Medical College Hospital from July 2002 to June 2004. It was found that high prevalence of diseases was in age group 20-29 years (36.03%) and females were the more suffered group (55.39%) than the males (44.61%). Among the different occupations, housewives ranked first (37.05%) and shows a definite association with fungal infections due to sweating (P